Assessment of repeat‐visit surveys as a viable method for estimating brood abundance at the 10.4‐km2 scale. (16th January 2018) - Carrlson, Kaylan M.; Gue, Charles Tanner; Loesch, Charles R.; Walker, Johann A.
ABSTRACT: Regional estimates of duck brood abundance could help conservation managers assess landscape productivity and thereby improve spatially explicit allocation of limited conservation funds in the Prairie Pothole Region. We assessed the utility of repeat‐visit brood counts from 2012 to 2013 surveys in the Prairie Pothole Region (ND, SD, and MT, USA) and hierarchical N‐mixture models for providing estimates of abundance at a 10.4‐km 2 scale. Models provided reliable estimates of brood abundance and underscored the importance of small wetlands and landscape characteristics to some dabbling duck broods in the Prairie Pothole Region. © 2018 The Wildlife Society. Abstract : Regional estimates of abundance could help conservation managers assess landscape productivity and thereby improve spatially explicit allocation of limited conservation funds. We demonstrated the utility of repeat‐visit surveys and hierarchical N‐mixture models for providing estimates of waterfowl brood abundance at a landscape scale within the Prairie Pothole Region.